1999
DOI: 10.1289/ehp.99107s2289
|View full text |Cite
|
Sign up to set email alerts
|

Asbestos and cancer: An overview of current trends in Europe.

Abstract: This review assesses the contribution of occupational asbestos exposure to the occurrence of mesothelioma and lung cancer in Europe. Available information on national asbestos consumption, proportions of the population exposed, and exposure levels is summarized. Population-based studies from various European regions on occupational asbestos exposure, mesothelioma, and lung cancer are reviewed. Asbestos consumption in 1994 ranged, per capita, between 0. 004 kg in northern Europe and 2.4 kg in the former Soviet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
43
0
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(48 citation statements)
references
References 49 publications
3
43
0
1
Order By: Relevance
“…3 Based on the historic trends in the incidence it has been estimated that the background rate without asbestos was at 1-2 per million, close to the Swedish female rates of 1 per million in the early period in our study. 15 This background would correspond to 20 male cases in a 5-year period, and 160 cases during the 8 5-year periods that our study covered. As the total number of male mesothelioma cases was 2190, 2,030 could be ascribed to asbestos up to year 2000.…”
Section: Dear Sirmentioning
confidence: 99%
“…3 Based on the historic trends in the incidence it has been estimated that the background rate without asbestos was at 1-2 per million, close to the Swedish female rates of 1 per million in the early period in our study. 15 This background would correspond to 20 male cases in a 5-year period, and 160 cases during the 8 5-year periods that our study covered. As the total number of male mesothelioma cases was 2190, 2,030 could be ascribed to asbestos up to year 2000.…”
Section: Dear Sirmentioning
confidence: 99%
“…The epidemiology of asbestos-related lung cancer (LC) cannot be investigated directly because cases are not clinically distinguishable from those due to other causes. The magnitude of the association and the attributable risk have been estimated in cohorts of workers exposed to asbestos and from LC case -control studies (Albin et al, 1999), but few studies have investigated it in the general population because generalisation of these findings is problematic (De Vos, 1993;Darnton et al, 2006). Ratios ranging from 1 : 1 to 1 : 10 between mesothelioma and excess LC deaths due to asbestos exposure have been reported in different cohorts of exposed workers (Vineis and Simonato, 1991).…”
mentioning
confidence: 99%
“…A review of European studies (including one in the area of Lund, Sweden) combining occupational histories with analyses of lung fiber content found that 62-85% of men with mesothelioma had probable occupational exposure to asbestos. 8 Perhaps in the Swedish study 1 the small number of male cases in agriculture/ gardening had less chance of a history (undocumented in the censuses) of occupational asbestos exposure than the small number of professionals and larger numbers of blue collar and non-asbestos manual workers (especially in urban areas). Otherwise, conjectures for the urban excess in Sweden vs. Connecticut would include differences in non-occupational asbestos exposure 1 (perhaps also in type and size of asbestos fibers) or in causes of mesothelioma other than asbestos.…”
mentioning
confidence: 87%